(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
Contributo sottoposto a valutazione SOMMARIO: 1. Premessa - 2. Le origini del concetto di attrezzatura religiosa - 3. Le previsioni regionali in materia e la loro successiva evoluzione - 4. Le problematiche aperte - 5. Alcuni risvolti pratici: le innovazioni di evidente impatto urbanistico in assenza di un previo esame ad opera della amministrazione comunale - 6. Osservazioni conclusive e possibili prospettive de iure condendo. Religious facilities and urban planning: lights and shadows Abstract In Italy many places of worship avoid the scope of planning regulations. This situation, especially for the places of Islamic worship (musalla), sometimes arises from the suspicion of local authorities to grant adequate space for the realization of these places; it sometimes arises also from the choice of the religious confessions. Therefore we face a difficult situation: you must guarantee the right to the free exercise of worship of the faithful in the area and at the same time you must comply with the provisions relating to urban planning, to protect other community needs, such as security or public order of the places. Keywords Religious confession, Church, Religious freedom, Planning law